The effect of dispersing agent on the dyeing of polyester fabrics with disperse dyes derived from 1,4-diethyl-2,6-dioxo-1,2,5,6-tetrahydropyridine-3-carbonitrile - Al-Etaibi, Alya; El-Apasery, Morsy Ahmed; Al-Awadi, Nouria (European Journal of Chemistry, 2013)
1,4-Diethyl-2,6-dioxo-1,2,5,6-tetrahydropyridine-3-carbonitrile (8), is synthesized by reacting ethyl cyanoacetate with ethyl amine to produce the amide 4, which when reacted with methyl propionylacetate, afforded compound 8. Compound 8 is then coupled with aromatic diazonium salts to give the corresponding arylhydrazono-1,4-diethyl-2,6-dioxo-1,2,5,6-tetrahydropyridine-3-carbonitrile disperse dyes, 11a-d, whose structures were elucidated by using X-ray crystal structure determinations. A high temperature dyeing method was employed to apply these dyes for polyester fabrics. The relationship between dyeing properties and the concentration of dispersing agent present in a dye bath is evaluated.